2019
DOI: 10.3390/md17100583
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Tandem Duplication Events Drive the Expansion of the C1q-Domain-Containing Gene Family in Bivalves

Abstract: C1q-domain-containing (C1qDC) proteins are rapidly emerging as key players in the innate immune response of bivalve mollusks. Growing experimental evidence suggests that these highly abundant secretory proteins are involved in the recognition of microbe-associated molecular patterns, serving as lectin-like molecules in the bivalve proto-complement system. While a large amount of functional data concerning the binding specificity of the globular head C1q domain and on the regulation of these molecules in respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 62 publications
1
26
0
Order By: Relevance
“…For the genes identified by both our study and the previous controlled exposure (complement C1q tumor necrosis factor-related protein 7-like and multimerin-2-like) we see an approximate sixfold increase in expression between the moderate-heavy and verylight infection categories. The role of these genes in immune responses is further supported by recent assessments of the functional role of these gene families in bivalve innate immunity (Gerdol et al, 2019). We also observed two versions of a ninjurin FIGURE 4 | Violin plots of interaction between gene body methylation and gene expression for 5,295 genes with both gene body methylation and expression data.…”
Section: Changes In Gene Expression In Response To P Marinus Infectisupporting
confidence: 73%
See 1 more Smart Citation
“…For the genes identified by both our study and the previous controlled exposure (complement C1q tumor necrosis factor-related protein 7-like and multimerin-2-like) we see an approximate sixfold increase in expression between the moderate-heavy and verylight infection categories. The role of these genes in immune responses is further supported by recent assessments of the functional role of these gene families in bivalve innate immunity (Gerdol et al, 2019). We also observed two versions of a ninjurin FIGURE 4 | Violin plots of interaction between gene body methylation and gene expression for 5,295 genes with both gene body methylation and expression data.…”
Section: Changes In Gene Expression In Response To P Marinus Infectisupporting
confidence: 73%
“…The positive association of infection of this gene within module Pink may suggest a role of angiogenesis in healing tissues degraded by P. marinus secreted proteases (La Peyre et al, 1995). In addition, multimerin-2-like genes have been proposed to have similar domains to complement component C1q genes (Gerdol et al, 2019) that were significantly differentially expressed in the above pairwise analysis of gene expression. In addition, two genes within this module, Thymosin beta-4 and kelch-like protein, have been associated with immune defense against pathogens, Thymosin beta-4 is also involved in antibacterial activity in C. gigas (Nam et al, 2015) and was found to facilitate the clearance of Vibrio alginolyticus in C. hongkongensi (Li et al, 2017).…”
Section: Changes In Gene Expression In Response To P Marinus Infectimentioning
confidence: 99%
“…As a result, 25 non-redundant CDK protein sequences including CDK1-10,CDK11B, CDK12-20, CDKL1-5 were identi ed in Bos taurus (Table 1). In parallel, 22,21,22,24,22,25 and 24 CDK family proteins were recognized in Bos grunniens, Hybrid-Bos Indicus, Hybrid-Bos taurus, Bos mutus, Bison bison bison, Bos indicus and Bubalus bubalis, respectively (Additional le 1) and the protein sequences of all the CDKs were provided in Additional le 2. Transcript ENSBIXT00000049337 is a newly identi ed member of CDK family in Hybrid-Bos taurus, which is named CDK20 according to the sequence similarity and collinearity.…”
Section: Identi Cation Of the Members In The Cdk Familymentioning
confidence: 99%
“…The family genes may distribute on different chromosomes or co-locate on the same chromosome, which are generally de ned as segmental duplication events in the former and tandem duplication events in the latter [23][24][25]. Chromosomal distributions of the CDK family genes showed that they located on 13 to 16 chromosomes in six species of bovidae, indicating both segmental and tandem duplication events have occurred for the expansion of CDK genes.…”
Section: Collinearity Analysis Of Cdks In Bovidaementioning
confidence: 99%
“…Related to the evolution of shells and the bivalve mollusk lifestyle 22 , 23 , the C1qDC gene of bivalve mollusks has undergone a massive expansion. The number of C1qDC genes in humans 24 , mice 25 , zebrafish 26 , and amphioxus 27 ranges from 29 to 52.…”
Section: Introductionmentioning
confidence: 99%